In-hospital and one-year outcomes in cancer patients receiving percutaneous coronary intervention for acute myocardial infarction: A real-world study - Tang, Manyun; Wang, Yidan; Cao, Xiangqi; Day, John D.; Liu, Hui; Sun, Chaofeng; Li, Guoliang (Frontiers in Cardiovascular Medicine, 2023)
Background: Cancer and ischemic heart disease are the leading causes of mortality. The optimal management for patients with concomitant acute myocardial infarction (AMI) and cancer remains challenging. Objective: To evaluate in-hospital and one-year adverse outcomes in cancer patients receiving percutaneous coronary intervention (PCI) to treat AMI. Methods: This was a single-center, retrospective cohort study, patients with cancer admitted to The First Affiliated Hospital of Xi’an Jiaotong University for AMI and discharged between January 2015 and June 2020 were analyzed. The outcomes were all-cause mortality at 1-year follow up and incidence of in-hospital adverse events, including arrhythmias, heart failure, major bleeding, stroke, and all-cause death. Results: A total of 119 patients were included, of these, 68 (57.1%) received PCI (PCI group) and 51 (42.9%) did not (non-PCI group). Patients in the PCI group had a lower incidence of in-hospital arrhythmias (22.1% vs. 39.2%; p=0.042), major bleeding (2.9% vs. 15.7%; p=0.013), and all-cause mortality (1.5% vs. 11.8%; p=0.018) than those in non-PCI group. On 1-year follow-up, the PCI group had a lower all-cause mortality than the non-PCI group (log-rank test=14.65; p<0.001). Multivariable Cox regression showed that PCI is an independent protective factor (adjusted HR=0.503 [0.243-0.947], p=0.045) for cancer patients who have concomitant AMI. Conclusions: Cancer patients receiving PCI for AMI had a lower risk of in-hospital adverse events and mortality as well as 1-year all-cause mortality compared to those who refused PCI. Our study therefore supports the use of PCI to improve prognosis of this selected group of patients.